Long‐Term Recruitment of Endogenous M2 Macrophages by Platelet Lysate‐Rich Plasma Macroporous Hydrogel Scaffold for Articular Cartilage Defect Repair. Issue 6 (7th January 2022) - Pan, Xiaoyun; Yuan, Shanshan; Xun, Xiaojie; Fan, Zhiyuan; Xue, Xinghe; Zhang, Changhuan; Wang, Jilong; Deng, Junjie
Abstract: After cartilage damage, a large number of monocytes/macrophages infiltrate into adjacent synovium and the resident macrophages in synovial tissue transform to activated macrophages (M1), which secrete pro‐inflammatory cytokines to induce sustained inflammation and chondrocyte apoptotic. However, current clinical therapies for cartilage repair can rarely achieve long‐term anti‐inflammatory regulation and satisfactory outcomes. Herein, a platelet lysate‐rich plasma macroporous hydrogel (PLPMH) scaffold with around 100 µm pore size and 1.25 MPa Young's modulus is developed to sustainedly recruit and polarize endogenous anti‐inflammatory macrophages (M2) for improving cartilage defect repair. PLPMH scaffold can steadily release sphingosine1‐phosphate and proteins via gradual degradation, thus inducing M2 macrophages migration or resting (M0) macrophages migration and then polarization to M2 phenotype, and improving the secretion of anti‐inflammatory cytokines. Furthermore, PLPMH scaffold exhibits negligible inflammatory responses in vivo and promotes endogenous M2 macrophage infiltration in large numbers and long‐time duration to provide a local anti‐inflammatory microenvironment, which even lasts for 42 d. In a rabbit model of cartilage defect, PLPMH scaffold increases the ratio of M2 macrophages and improves cartilage tissue regeneration. These studies support that PLPMH scaffold may have a great potential in articular cartilage tissue engineering by providing an anti‐inflammatory and pro‐regenerative microenvironment. Abstract : A platelet lysate‐rich plasma macroporous hydrogel scaffold is prepared, which sustainedly recruits and polarizes endogenous anti‐inflammatory M2 macrophages via releasing of sphingosine1‐phosphate and proteins, thus improving the secretion of anti‐inflammatory cytokines and providing a long‐time local anti‐inflammatory microenvironment for cartilage defect repair.